Puberty marks major changes in the hippocampal and cortical c-Fos activation pattern induced by NMDA receptor antagonists. (January 2017) - Inta, Ioana; Domonkos, Emese; Pfeiffer, Natascha; Sprengel, Rolf; Bettendorf, Markus; Lang, Undine E.; Inta, Dragos; Gass, Peter
Abstract: Non-selective and subunit (GluN2B)-specific N -methyl-d -aspartate receptor (NMDAR) antagonists represent promising alternative antidepressant drugs with fast onset of the therapeutic action. The neuronal activation pattern induced by NMDAR antagonists is well characterized by c-Fos expression analysis only in the adult rodent brain. In contrast, there is little information available regarding their effects during postnatal development. Here we performed a systematic c-Fos brain mapping of the non-selective NMDAR antagonist MK-801 and the GluN2B-specific antagonist Ro 25-6981 from postnatal day 16 (P16) to P40. We found significant regional differences with gender-specificity in the activation pattern compared to the adult. Surprisingly, in the hippocampus, MK-801 triggered at pre-pubertal stages (especially at P24) very strong c-Fos expression, followed by low levels after P30, the approximate time point of puberty onset in mice. The cortical distribution of MK-801-triggered c-Fos expression before puberty differed also substantially from the adult brain, showing high levels only in deep cortical layers at pre-pubertal stages. In comparison, the cortical activation induced by Ro 25-6981 diminished from high pre-pubertal levels and was in comparison with that triggered by MK-801 low in the hippocampus. These results reveal highly dynamic changes in the c-Fos activation pattern induced by NMDAR antagonists during puberty. This article is part of the Special Issue entitled 'Ionotropic glutamate receptors'. Highlights: The brain activation pattern induced by NMDAR blockade during puberty is unknown. We found high hippocampal c-Fos activation by MK-801 at postnatal day 24. Cortical MK-801-induced activation changed from deep to all layers during puberty. GluN2B-specific antagonists triggered activation patterns distinct from MK-801.